Hubungan Mutu Pelayanan Kesehatanm Dengan Kepuasan Pasien Di Upt Puskesmas Bestari Kota Medan Tahun 2024 - Elvi Andriany Simbolon; Kesaktian Manurung; Janno Sinaga; Donal Nababan; Frida Lina Tarigan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Health is one of the basic needs of society which is very important in supporting daily activities. As people's living standards increase, so do people's needs, hopes and demands for quality health. This situation requires health service providers such as hospitals to improve the quality of services better and provide satisfaction for consumers as users of health services. The problem formulation in this research is